2021
DOI: 10.3389/fimmu.2020.620417
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time PCR Assay for the Diagnosis of Intestinal Schistosomiasis and Cure Assessment After the Treatment of Individuals With Low Parasite Burden

Abstract: The laboratorial diagnosis of the intestinal schistosomiasis is always performed using Kato-Katz technique. However, this technique presents low sensitivity for diagnosis of individuals with low parasite burden, which constitutes the majority in low endemicity Brazilian locations for the disease. The objective of this study was developed and to validate a real-time PCR assay (qPCR) targeting 121 bp sequence to detect Schistosoma spp. DNA for the diagnosis of intestinal schistosomiasis and a sequence of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
1
11
0
4
Order By: Relevance
“…Based on the results from the “reference test” (24 Kato-Katz slides + Saline Gradient method-SG) the qPCR presented 82.6%, 93.1%, and 89.8% of sensitivity, specificity, and accuracy rates, respectively. The positivity of qPCR was higher than that of the 24 Kato-Katz slides, SG techniques ( 103 ) or Kato-Katz and Spontaneous Sedimentation techniques combined ( 148 ) when tested in a low endemicity area. As the number of infection intensity reduces and the number of epg of feces becomes smaller ( 149 ), there is an increased likelihood of discrepant results between PCR-based assays and parasitological tests.…”
Section: Diagnosis Of Schistosoma Species Infectionsmentioning
confidence: 81%
See 3 more Smart Citations
“…Based on the results from the “reference test” (24 Kato-Katz slides + Saline Gradient method-SG) the qPCR presented 82.6%, 93.1%, and 89.8% of sensitivity, specificity, and accuracy rates, respectively. The positivity of qPCR was higher than that of the 24 Kato-Katz slides, SG techniques ( 103 ) or Kato-Katz and Spontaneous Sedimentation techniques combined ( 148 ) when tested in a low endemicity area. As the number of infection intensity reduces and the number of epg of feces becomes smaller ( 149 ), there is an increased likelihood of discrepant results between PCR-based assays and parasitological tests.…”
Section: Diagnosis Of Schistosoma Species Infectionsmentioning
confidence: 81%
“…A cross-sectional study identified S. haematobium eggs in semen of fishermen, demonstrating the lodgment of eggs in the reproductive system with the implication that quantification of infection burden using urine alone may underestimate infections ( 91 ). Although the positivity rate of Kato-Katz is directly proportional to the number of slides and fecal samples examined ( 103 , 104 ), it is logistically challenging in large epidemiological studies to examine multiple replicate slides. Given that the WHO recommends that stool sampling be done on three consecutive days to have a reliable analysis brings to the fore how challenging this is in resource limited settings ( 105 ).…”
Section: Diagnosis Of Schistosoma Species Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of molecular diagnostic technology, nucleic acid detection methods including conventional polymerase chain reaction (PCR) [ 19 ], nested PCR [ 20 ], real-time PCR [ 21 , 22 , 23 ], digital PCR [ 24 ], and so on [ 25 ], presenting high detection specificity and sensitivity [ 26 , 27 ], provide a new idea for the diagnosis of schistosomiasis. However, these PCR-based techniques require expensive equipment and skilled personnel, which are rarely available in schistosomiasis endemic areas featured by poverty and scarce of resources [ 28 ].…”
Section: Introductionmentioning
confidence: 99%